Perilaku Perawat Anestesi Dalam Pencegahan Cedera Pada Pasien Di Instalasi Bedah Sentral - Nuryanti, Aprilia; Trisnowati, Tatik (Yayasan Jompa Research and Development, 2025)
Anaesthesia-related injuries are a critical issue that can occur during procedures, whether in general, local, or regional anaesthesia. These complications can lead to physical injury, such as nerve injury, airway injury, or even death. Anaesthesia nurses play a strategic role in preventing injuries through the implementation of safe and standardised anaesthesia practices. This study used a quantitative descriptive design with a survey approach to describe the behaviour of anaesthesia nurses in preventing anaesthesia injuries in the Central Surgical Unit (CSU). The population in this study were nurses/anaesthesia technicians working in the central surgical units of hospitals in Indonesia. Sampling was conducted using quota sampling of 100 nurses/anaesthetists who completed an online electronic questionnaire. The results of the anaesthesia injury prevention behaviour measuring indicated that most respondents (76%) were in the ‘very good’ category, with the highest score on the indicator of checking the completeness and functionality of anaesthesia machines before the procedure (94%). Other indicators that were also high were checking anaesthesia equipment (91%) and preparing drugs/fluids according to the type of anaesthesia (91%). Meanwhile, compliance with anaesthesia protocol safety procedure received the lowest percentage in the very good category among other behavioural indicators (77%). Improvement efforts can be conducted through continuous training, workload management improvements, strengthened team communication, and adjustments to the ratio of anaesthesia personnel to the number of operations.